Effectiveness of an individualized training based on dynamic strength index on sprinting, jumping and change of direction performance in basketball players: A randomized controlled trial - Pleša, J.; Ujakovic, F.; Ribic, A.; Bishop, C.; Šarabon, N.; Kozinc, Ž. (Journal of Sports Science & Medicine, 2024)
The dynamic strength index (DSI) is calculated as the ratio between countermovement jump (CMJ) peak force and isometric mid-thigh pull (IMTP) peak force and is said to inform whether ballistic or strength training is warranted for a given athlete. This study assessed the impact of an individualized in-season resistance training program, guided by DSI on basketball players` physical performance. Forty-three elite players (19.4 ± 2.9 years; 1.97 ± 0.08 cm; 89.1 ± 9.5 kg) were divided into an intervention group (IG) (27 players) and a control group (CG) (16 players). The IG was further split based on DSI into a ballistic group (DSI = 0.90, 11 players) and a strength group (DSI > 0.90, 16 players). Over five weeks, participants underwent two weekly resistance sessions, with the IG following a DSI-based program and the CG a standard program. Performance was measured pre- and post-intervention through 20-m sprints, 505 change of direction test, CMJ, and IMTP. There were statistically significant improvements in the IG, notably in sprint times (n2 = 0.12-0.21, p < 0.05) and 505 test (n2 = 0.15-0.16, p < 0.05), predominantly in the strength group. The CG`s performance was either unchanged or declined for different variables. Our results suggest that DSI-guided training effectively enhances basketball players` physical performance within a competitive season.